2003
DOI: 10.1530/eje.0.1480233
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum inhibin A levels are a marker of a viable trophoblast in incomplete and complete miscarriage

Abstract: Objective: From early gestation the human trophoblast secretes large amounts of inhibin A and activin A, and their measurement provides a value for predicting the outcome in women who become pregnant after assisted reproductive techniques. The aim of the study was to investigate the putative role of maternal serum inhibin A and activin A levels as markers of a viable trophoblast in women who miscarry. Design: Controlled cross-sectional study. Methods: One group consisted of 65 healthy pregnant women (controls)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 18 publications
1
14
0
2
Order By: Relevance
“…Activin A levels are reduced in the presence of nonviable trophoblast [1719], and single and serial measurements have been used to predict miscarriage [8]. Furthermore, it has been suggested that lower activin A in EP compared with those other failed pregnancies may be due to the difficulty of the ectopic trophoblast to correctly implant, compromising the decidualization process, and that some EPs could have more active trophoblasts and behave more like IUPs, whilst others will be failing and behave like failing MAs [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activin A levels are reduced in the presence of nonviable trophoblast [1719], and single and serial measurements have been used to predict miscarriage [8]. Furthermore, it has been suggested that lower activin A in EP compared with those other failed pregnancies may be due to the difficulty of the ectopic trophoblast to correctly implant, compromising the decidualization process, and that some EPs could have more active trophoblasts and behave more like IUPs, whilst others will be failing and behave like failing MAs [12].…”
Section: Discussionmentioning
confidence: 99%
“…Both factors are involved in the complex mechanisms allowing the establishment and the maintenance of pregnancy. Their serum concentrations rise throughout viable pregnancy [5, 6] and decline in a state of nonviable trophoblasts [1720]. Furthermore, their serum concentrations are significantly lower in serial measurements in women who subsequently miscarried when compared with live births [11, 1921].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the human placenta is a relevant source of activin A since early pregnancy [25] and, variations in maternal activin A levels are common in trophoblast diseases as in the case of complete miscarriage [26][27][28]. Nevertheless, these evidences together would suggest that a reduction of activin A secretion may signal the difficulty of the trophoblast to correctly implant.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential maternal serum markers currently highlighted was inhibin A. Johns et al found that after controlling for serum -hCG level, inhibin A was the only predictor for miscarriage [15]. Inhibin A and -hCG are two substances produced by the growing trophoblast and lower level of these two hormones was associated with miscarriage [16].…”
Section: Discussionmentioning
confidence: 99%